Lack of Toxic Interaction between Fusariotoxins in Broiler Chickens Fed throughout Their Life at the Highest Level Tolerated in the European Union - Metayer, Jean-Paul (Toxins (Basel), 2019)
Fusarium mycotoxins (FUS) occur frequently in poultry diets, and regulatory limits are laid down in several countries. However, the limits were established for exposure to a single mycotoxin, whereas multiple contamination is more realistic, and different studies have demonstrated that it is not possible to predict interactions between mycotoxins. The purpose of this study was thus to compare the toxic effect of deoxynivalenol (DON), fumonisins (FB) and zearalenone (ZON), alone and in combination on broiler chickens, at the maximum tolerated level established by the EU for poultry feed. Experimental corn-soybean diets incorporated ground cultured toxigenic Fusarium strains. One feed was formulated for chickens 0 to 10 days old and another for chickens 11 to 35 days old. The control diets were mycotoxin free, the DON diets contained 5 mg DON/kg, the FB diet contained 20 mg FB1 + FB2/kg, and the ZON diet contained 0.5 mg ZON/kg. The DONFBZON diet contained 5, 20, and 0.5 mg/kg of DON, FB1 + FB2, and ZON, respectively. Diets were distributed ad libitum to 70 broilers (male Ross PM3) separated into five groups of 14 chickens each reared in individual cages from one to 35 days of age. On day 35, after a starvation period of 8 h, a blood sample was collected, and all the animals were killed and autopsied. No difference between groups that could be attributed to FUS was observed in performances, the relative weight of organs, biochemistry, histopathology, intestinal morphometry, variables of oxidative damage, and markers of testicle toxicity. A significant increase in sphinganine and in the sphinganine to sphingosine ratio was observed in broilers fed FB. Taken together, these results suggest that the regulatory guidelines established for single contamination of broiler chickens fed with DON, FB, and ZON can also be used in the case of multiple contamination with these toxins.